Realisation of security for the internet of things - Aung Naing Oo (2016)
Internet of Things or IoT is the next big leap in the field of Information Technology. What is so special about it is that billions of devices will be able to talk to each other and to the users conveying information that is of interest. These devices would be uniquely addressable and would contain live information on the data that they hold depending on the environment where they are deployed. Some of the devices that we see in the market today are smart watches, door locks, light bulbs and much more. One sure thing is that more and more such devices would emerge by the end of this decade. It will not be just limited to smart homes but we would also be noticing wide usage in the industries from manufacturing to R&D. With so much hype, users are already concerned about security and privacy related issues when it comes to IoT. Standards and Regulations are still yet to be finalized by official bodies on these issues. Meanwhile, researchers are coming up with different suggestions on the best practices to be used when building these devices. One common point of agreement among them is that security must be built from the very initial stage of design. In this paper, we take a look at the kind of security practices that we may exercise when hooking up IoT devices at home. One of the section displays an innovative mash up between two very different fields of Security and Information Retrieval by using a piece of technology from the latter into the former. Further on, it becomes even more interesting when we visualize encrypted live data from sensors on one end of the network to a web page on the other end. It is of utmost importance that any crucial data be strongly encrypted from end to end, which means, any data that leaves from one point must leave in encrypted format and be only decrypted on the receiving end provided that the receiving party has the correct credentials. The report also sheds some light at vulnerabilities of existing practices and introduces the usage of Virtual Private Network technology.